2023
DOI: 10.1037/ocp0000354
|View full text |Cite
|
Sign up to set email alerts
|

What are the active ingredients in recovery activities? Introducing a dimensional approach.

Khalid M. Alameer,
Sjir Uitdewilligen,
Ute R. Hülsheger

Abstract: Although previous research suggests that off-job activities are generally important for recovery from work stress, a profound understanding of which aspects of recovery activities benefit the recovery process and why is still lacking. In the present work, we introduce a dimensional approach toward studying recovery activities and present a taxonomy of key recovery activity dimensions (physical, mental, social, spiritual, creative, virtual, and outdoor). Across four studies (total N = 908) using cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 141 publications
(293 reference statements)
0
4
0
Order By: Relevance
“…Thus, relaxation after work should increase employees' next-morning vigor. In contrast, mastery experiences arise from more challenging activities (e.g., physical or creative activities; Alameer et al, 2023) and give employees a feeling of competency. Thus, experiencing mastery can feel energizing and uplifting (van Hooff & De Pater, 2019;Vandercammen et al, 2014).…”
Section: Interpersonal Conflicts Recovery Experiences and Next-mornin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, relaxation after work should increase employees' next-morning vigor. In contrast, mastery experiences arise from more challenging activities (e.g., physical or creative activities; Alameer et al, 2023) and give employees a feeling of competency. Thus, experiencing mastery can feel energizing and uplifting (van Hooff & De Pater, 2019;Vandercammen et al, 2014).…”
Section: Interpersonal Conflicts Recovery Experiences and Next-mornin...mentioning
confidence: 99%
“…These results underline that dealing with the physiological stress reaction following interpersonal conflicts limits employees' energetic and self-regulatory resources, which are subsequently not available for mastering challenges (Baumeister et al, 2019;Nixon et al, 2011). Considering the diverging results for mastery and relaxation, recent research has demonstrated that different recovery activities underly relaxation and mastery experiences (Alameer et al, 2023).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…self-efficacy; Sonnentag and Fritz, 2007), employees must engage in challenging and effortful nonwork activities if they are to experience mastery. For example, employees may experience mastery when they engage in nonwork activities that involve mental, physical, and/or creative effort (Alameer et al, 2023), such as doing sports or learning an instrument. Engagement in these activities requires the investment of personal resources (Sonnentag and Fritz, 2007).…”
Section: Leading For Growthmentioning
confidence: 99%